2015
DOI: 10.1161/circresaha.116.303356
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Drp1 Mediates Mitochondrial Autophagy and Protects the Heart Against Energy Stress

Abstract: Editorial, see p 225Mitochondria are dynamic organelles that constantly undergo fusion and fission 5 to adapt to changes in the cellular environment. Although mitochondrial fusion allows mitochondria to maintain membrane potential by fusing depolarized mitochondria to intact ones, fission allows the segregation of unrecoverable mitochondria so that they can be eliminated by autophagy or mitophagy, a specialized form of autophagy.6 Mitochondrial fusion is critically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
491
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 483 publications
(513 citation statements)
references
References 37 publications
19
491
3
Order By: Relevance
“…Studies demonstrated that suitable mitochondrial fission is required for damaged mitochondria before removal by mitophagy in mouse pancreatic β cells (Twig et al ., 2008). Besides, downregulation of DLP1 has been reported to prevent mitochondrial autophagy in mouse heart (Ikeda et al ., 2015; Shirakabe et al ., 2016). DLP1 has also been described to modulate mitophagy, possibly involving the interaction of DLP1 with the mitophagy receptor FUN14 domain‐containing 1 Pan troglodytes (FUNDC1) (Zuo et al ., 2014; Wu et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that suitable mitochondrial fission is required for damaged mitochondria before removal by mitophagy in mouse pancreatic β cells (Twig et al ., 2008). Besides, downregulation of DLP1 has been reported to prevent mitochondrial autophagy in mouse heart (Ikeda et al ., 2015; Shirakabe et al ., 2016). DLP1 has also been described to modulate mitophagy, possibly involving the interaction of DLP1 with the mitophagy receptor FUN14 domain‐containing 1 Pan troglodytes (FUNDC1) (Zuo et al ., 2014; Wu et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of this process is mitochondrial turnover, which refers to the integrated processes of degradation via autophagy (mitophagy) and biogenesis. We and others previously demonstrated the importance of cardiac mitophagy in attenuating I/R-induced injury (2)(3)(4). A considerable amount of preclinical evidence that mitochondrial biogenesis programs are activated in the setting of cold cardioplegia or I/R has been reported (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, MB promotes mitophagy by maintaining the MMP at a relatively high level, which contributes to a decrease in necrosis and an improvement in neurological function, thereby protecting against ACI injury. leads to mitochondrial dysfunction (16,17). Dysfunctional mitochondria can be selectively eliminated via mitophagy (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%